Imaginary money against sticky relative prices - Eduardo Loyo (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2001)
This paper considers price setting in pure units of account, linked to the means of payment through managed parities. If prices are sticky in the units in which they are set, parity changes may facilitate equilibrium adjustment of relative prices. The paper derives simultaneously the optimal choice of unit of account by each price setter, and the optimal parity policy. The gains from having multiple units of account are computed for a simple calibrated economy.
Keywords: E4; E5; F4; 330